2012
DOI: 10.2105/ajph.2012.300777
|View full text |Cite
|
Sign up to set email alerts
|

Trust, Medication Adherence, and Hypertension Control in Southern African American Men

Abstract: We examined the relationship between trust in the medical system, medication adherence, and hypertension control in Southern African American men. The sample included 235 African American men aged 18 years and older with hypertension. African American men with higher general trust in the medical system were more likely to report better medication adherence (odds ratio [OR] = 1.06), and those with higher self-efficacy were more likely to report better medication adherence and hypertension control (OR = 1.08 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 31 publications
3
55
1
2
Order By: Relevance
“…We observed no correlation between trust and the duration of relationship with the psychiatrist among our patients despite the reports of positive correlations between the length of time in the patient-physician relationship and trust scores (Kao et al, 1998;Doescher et al, 2000). The positive correlation between trust and medication adherence in our data has been confirmed in previous studies (Elder et al, 2012;Abel and Efird, 2013;Schoenthaler et al, 2013).…”
Section: Itemsupporting
confidence: 82%
“…We observed no correlation between trust and the duration of relationship with the psychiatrist among our patients despite the reports of positive correlations between the length of time in the patient-physician relationship and trust scores (Kao et al, 1998;Doescher et al, 2000). The positive correlation between trust and medication adherence in our data has been confirmed in previous studies (Elder et al, 2012;Abel and Efird, 2013;Schoenthaler et al, 2013).…”
Section: Itemsupporting
confidence: 82%
“…23 Elder et al found greater trust to be independently associated with better medication adherence among another sample of African Americans with hypertension, while perceived racial discrimination was not independently associated with adherence in the tested model. 24 Saha et al found that trust was independently associated with greater adherence to anti retroviral therapy among a cohort of patients with HIV, and that accounting for trust reduced the magnitude of disparities in HIV care among black and white HIV patients. 25 SCD patients experience many problems with the interpersonal quality of their care from healthcare providers, and these problems have an impact on the trust that SCD patients have in the medical profession.…”
Section: Discussionmentioning
confidence: 99%
“…The results also suggested that poor adherence would decrease by 23 % for every one unit increase in self-effi cacy ( P = 0.010). Similarly, Elder et al showed similar results in a cross-sectional study of 235 Southern AA men where those with higher self-effi cacy scores were more likely to have better adherence (OR = 1.08) [ 26 ].…”
Section: Patient-related Factorsmentioning
confidence: 63%
“…In a cross-sectional study of 993 participants with hypertension [820 AA (585 women, 235 men) and 173 white], trust, medication adherence, and blood pressure control were evaluated in the subset of AA men. Logistic regression models showed that AA men with higher levels of general trust in the medical system were more likely to self-report better adherence (OR = 1.06, P = 0.027) [ 26 ].…”
Section: Health Care Team-related Factorsmentioning
confidence: 99%